Checklist of mosses from southern part of Maliau Basin conservation area, Sabah, East Malaysia - Monica Suleiman; Hiroyuki Akiyama (Institute for Tropical Biology and Conservation, 2007)
A total of 86 taxa in 40 genera and 20 families of mosses were collected fiom southem part of Maliau Basin Consevation Area, Sabah, Malaysia, during three separate expeditions held in 1996, 1999 and 2001. This represents about 15% of the reported mosses from Sabah. Two species are new records for Borneo, Clastobryum cuculligerum (Sande Lac.) Tixier and Syrrhopodon parasiticus (Brid.) Besch., while three are new to Sabah, Ieucobryum bowringii Mitt, Syrrhopodon sarawakensis (Dixon) W.D.Reese and Trismegistia korthalsii (Dozy & Molk.) Broth.